已知-m+2n=5,那么(m-2n)^2+6n-3m-60=
1个回答
答:
-m+2n=5
(m-2n)²+6n-3m-60
=(-m+2n)²+3(2n-m)-60
=5²+3*5-60
=25+15-60
=-20
相关问题
已知-m+2n=5,那么5(m-2n)^2+6n-3m-60的值为( )
已知:-m+2n=5,那么4(m-2n)2+6n-3m-60的值为______.
已知-m+2n=5,那么3(m-2n)的平方+6n-3m-60的值是
已知-m+2n=5,那么5(m-2n)的平方+6n-3m-60的值为( ),快
已知-m+2n=5,求:5(m-2n)2+6n-3m-60的值?
已知M-2N=5,那么3(2N-M)²=5M-10N=_______
已知|2m-5|+(2m-5n+20)^2=0,求(-2m^2)-2m(5n-2m)+3n(6m-5n)-3n(4m-5
已知 |2m-5|+(2m-5n+20)的平方=0 求-2m²-2m(5n-2m)+3n(6m-5n)-3n(
已知3/4M=2/3N那么M:N=( ):( ),N/M=
已知 |2m-5|+(2m-5n+20)的平方=0 求-2m的平方-2m(5n-2m)+3n(6m-5n)-3n(4m-